An Estimation of Tree Species Diversity in Rural Farmland of Nepal - Kharal, Deepak K; Oli, Bishwa N (Banko Janakari, 2009)
Biodiversity is an important consideration in maintaining natural environmental balance in a particular habitat. This becomes particularly important in areas, where due to the encroachment of natural forests, biodiversity is depleting causing a potential loss in the natural habitat. In such a situation, biodiversity in the farmland becomes an important consideration. Biodiversity is measured and analyzed using various indices. In this study, we present the result of our study through a field work in a rural village in Nepal. The study was conducted through direct field observation and survey of sampled households. The status of tree biodiversity using species biodiversity index and species richness index for the case study are presented. The study has also identified the relationship between the tree species diversity and major socioeconomic factors. Our analysis shows that tree species biodiversity in the rural farmland of study area are lower in comparison to the similar areas of countries like India, Bangladesh and Sri Lanka. The lower biodiversity status is mainly due to the wide distribution of two dominating tree species of Dalbergia sissoo and Melia azederach. Similarly, Tree species biodiversity in the farm land has been found affected by the socioeconomic situation of the area. Further study is suggested by involving more socioeconomic factors and covering a large sample size and time of study. Key words: Farmland, Forest, Homegarden, Nepal, Species Diversity, Species Richness, Trees. doi: 10.3126/banko.v18i1.2160 Banko Janakari, Vol. 18, No. 1, 3-10